Autoliderazgo escolar y comunicación efectiva en estudiantes de v ciclo de nivel primaria en la i. E. de acción conjunta Nuestra Señora de Loreto, Nauta 2023 - Gomez Zumaeta, Elita Estefani (2024)
The primary goal of this research was to investigate the relationship between school self-leadership and effective communication among 5th-grade students at the Joint Action Educational Institution "Nuestra Señora de Loreto Nauta" in 2023. Methodology: The approach was relational, utilizing a non-experimental, field based, cross-sectional, and bivariate design. Data were collected using a survey administered to 194 students, who comprised both the study's population and sample. The questionnaires were previously validated to ensure the reliability of the collected data. Results: Statistical analysis revealed a positive and statistically significant correlation between school self-leadership and effective communication. Notably, the Kendall’s Tau-b coefficient was 6.818 with a significance level of 0.000 (p < 0.05), indicating that an increase in student self-leadership is linked to enhancements in their communicative abilities. Conclusion: The study's findings confirm that the development of self-leadership is intricately connected to the students’ ability to communicate effectively. This underscores the importance of fostering self-leadership as a key strategy for boosting effective communication skills within the educational context.